2017
DOI: 10.3390/rs9090887
|View full text |Cite
|
Sign up to set email alerts
|

Sea Wind Measurement by Doppler Navigation System with X-Configured Beams in Rectilinear Flight

Abstract: Abstract:We suggest a conceptual approach to the measurement of the near-surface wind vector over water using a Doppler navigation system, in addition to its standard navigation capabilities. We consider a Doppler navigation system with a track-stabilized antenna and x-configuration of its beams. For the measurement of the sea-surface wind, the system operates in the multi-beam scatterometer mode in rectilinear flight. The proposed conceptual design has been validated, and its accuracy for the wind vector meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Recently, it has been shown that a Doppler navigation system (DNS) operated as a four-beam scatterometer is feasible for wind speed and direction retrieval [19]. The best beams geometry Remote Sens.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Recently, it has been shown that a Doppler navigation system (DNS) operated as a four-beam scatterometer is feasible for wind speed and direction retrieval [19]. The best beams geometry Remote Sens.…”
Section: Resultsmentioning
confidence: 99%
“…Simulations for different numbers of beams have been performed such that the total number of the "measured" NRCS samples obtained by all beams in the considered star configuration was either identical or very close to each other, in particular 20000 for the 30 • incidence angle, and 6260 at the incidence angles of 45 • or 60 • . A higher number of NRCS samples used at the 30 • incidence angle is required due to the lower sensitivity for the wind retrieval at that incidence angle compared with higher incidence angles [19]. The results are shown for either no instrumental noise or with 0.1 dB noise at the incidence angle of 30 • and 0.2 dB noise at the incidence angles of 45 • and 60 • .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently in [37], we have demonstrated that in order to provide an accurate and unambiguous retrieval of the wind vector, at least four azimuthally star-configured beams (looks) are required at the same incidence angle. The airborne star geometry [38] and some other earlier considered airborne one- [39] or multi-beam [40][41][42][43] geometries or sector scanning airborne instruments operated in the scatterometer mode [44][45][46][47][48][49] cannot be implemented for the satellite scatterometer to observe the same cell and to achieve better sea ice and water discrimination. Therefore, using the azimuthal isotropy of the sea ice backscattering in contrast to the anisotropy of the water surface backscattering, we considered another five hypothetical, fixed fan-beam scatterometer geometry constructed by adding an "extra" fore-antenna and an "extra" aft-antenna having 32.5 • and 147.5 • azimuthal directions relative to the spacecraft ground track, respectively, [25] as presented in Figure 3.…”
Section: Methodsmentioning
confidence: 99%